Norwegian Wood - Murakami, Haruki (New York, Vintage International, 2012)
"Toru, a quiet and preternaturally serious young college student in Tokyo, is devoted to Naoko, a beautiful and introspective young woman, but their mutual passion is marked by the tragic death of their best friend years before. Toru begins to adapt to campus life and the loneliness and isolation he faces there, but Naoko finds the pressures and responsibilities of life unbearable. As she retreats further into her own world, Toru finds himself reaching out to others and drawn to a fiercely independent and sexually liberated young woman"
Keywords: College students--Japan--Tokyo--Fiction.; Tokyo (Japan)--Fiction.